Spatial Utilization Pattern for Sasirangan Craftsmen's House in Sasirangan Village, Banjarmasin - Aula Sekar Arum Pertiwi; Damayanti Asikin; Lisa Dwi Wulandari; Khairunnisak Khairunnisak; Rafika Hilmi Nasution; I Gede Wyana Lokantara; Zhilli Izzadati Khairuni; Siti Zulfa Yuzni (Department of Urban and Regional Planning, Universitas Diponegoro, 2025)
The Seberang Masjid region is one of the last places that still looks like Banjar Village, and it has a unique art called sasirangan cloth. The government and the corporate sector changed the name of the region to Kampung Sasirangan in 2010 to make local knowledge more valuable. This development affects the change in the role of homes, which are now used for more than just living in. They are now used for business and manufacturing. The several steps in making sasirangan cloth affect how craftspeople act, which in turn affects how the company house uses space. This study seeks to identify and analyse the spatial utilization patterns in the residences of sasirangan textile craftspeople in Kampung Sasirangan, Banjarmasin. The research methodology employed is a case study utilizing a qualitative approach, incorporating field observation, in-depth interviews, and documentation. The results show that there are 17 craftsmen's houses on the land, along the riverbanks, and above the river. There are two primary ways that space is used: one building mass and two building masses. Craftsmen do not have a separate place to work; instead, they make the most of the space they already have by changing it to fit the stage of production. Craftsmen who have more complicated production stages use space in a wider range of ways.